2002
DOI: 10.1051/rnd:2002007
|View full text |Cite
|
Sign up to set email alerts
|

Major constituents, leptin, and non-protein nitrogen compounds in mares' colostrum and milk

Abstract: -Five Haflinger mares were hand-milked at 0 h (pre-suckle) and 6 h (postsuckle), 12, 24, 48, 72 and 96 h after parturition. Total solids, protein, fat, lactose, calculated gross energy content, leptin and non-protein nitrogen components (urea, a-amino nitrogen, creatinine and allantoin) were determined. The levels of the major constituents differed significantly in pre-suckle colostrum from subsequent samples. Leptin levels were the highest in whole (9 ng . mL -1 of immunoreactive human equivalent HE ± 0.48 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
5
31
2
Order By: Relevance
“…Among the NPN components of equid milk, the average urea content (20e35 mg 100 g À1 ) is consistent with data from cow milk, but slightly lower than those from human milk (Darragh & Lonnerdal, 2011;Dell'Orto et al, 1994;Fantuz et al, 2009b;Martuzzi et al, 2004;O'Connell & Fox, 2011) and it represents approximately 40% of the NPN fraction in horse and donkey milk (Fantuz et al, 2009b;Salimei, Varisco, & Rosi, 2002). This could be related to the different metabolic abilities among mammalians in recycling urea.…”
Section: Nitrogenous Componentssupporting
confidence: 71%
See 1 more Smart Citation
“…Among the NPN components of equid milk, the average urea content (20e35 mg 100 g À1 ) is consistent with data from cow milk, but slightly lower than those from human milk (Darragh & Lonnerdal, 2011;Dell'Orto et al, 1994;Fantuz et al, 2009b;Martuzzi et al, 2004;O'Connell & Fox, 2011) and it represents approximately 40% of the NPN fraction in horse and donkey milk (Fantuz et al, 2009b;Salimei, Varisco, & Rosi, 2002). This could be related to the different metabolic abilities among mammalians in recycling urea.…”
Section: Nitrogenous Componentssupporting
confidence: 71%
“…Furthermore, in horse and donkey mammary secretion, defatted or not, growth factors and hormones have also been determined through radioimmunoassay or ELISA methods that use human peptides as standard and specific antibodies, properly validated for the equid species. In detail, horse and donkey mammary secretions contain human-like leptin at levels (3.35e5.32 ng mL À1 milk; Salimei et al, 2002Salimei et al, , 2005bSalimei, Rosi, Maglieri, Magistrelli, & Fantuz, 2007) close to human milk (Bonnet et al, 2002). The bioactive peptides insulinlike growth factor 1 (IGF-1, 9.81e13.50 ng mL À1 milk), ghrelin (4.26e4.63 pg mL À1 milk; Magistrelli, Rosi, Amicone, Maglieri, & Salimei, 2008) and triiodothyronine (T3, 4.0 ng mL À1 milk; Todini, Malfatti, Salimei, & Fantuz, 2010) were also found in frozen donkey milk.…”
Section: Functional and Bioactive Componentsmentioning
confidence: 99%
“…Similarly, increased milk production in draft mares could account for the growth advantage in P-D foals, since milk yields are known to be breed specific [61] and to be increased with the mare's size [61]. Hormones and growth factors such as T 3 [62], leptin [63], IGF-1 and insulin [64] and thyroid stimulating hormone (TSH) [49] are also supplied through the mare's colostrum. In Quarter horses, milk leptin, IGF-1 and TSH concentrations were at their maximum the day of parturition and reached minimum at 2 months postpartum (leptin and TSH) or became undetectable by 12 days postpartum (IGF-1) [49].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Salimei et al (2002) on mare's mammary secretion (multiparous Haflinger) showed a significant increase of the fat content in the first 6 h from foaling reaching 2.49%. After 12 h from foaling the fat Fatty acids: SFA (saturated fatty acids) -sum of SCFA + MCSFA + LCSFA.…”
Section: Discussionmentioning
confidence: 99%
“…The colostral period of mares was found to be much shorter than that of cows and the colostrum showed significant differences from normal milk only Available online at www.sciencedirect.com Livestock Science 113 (2008) 285 -290 www.elsevier.com/locate/livsci on the first day after foaling. Salimei et al (2002) showed a significant increase of the fat content in the first 6 h from foaling. The dry matter content of mares' milk decreased drastically from colostrum to normal milk, due, primarily, to a decrease in protein content.…”
Section: Introductionmentioning
confidence: 94%